2015
DOI: 10.1371/journal.pone.0129250
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Discrimination of Alzheimer’s Disease Based on Regional Cortical Atrophy and Hypometabolism

Abstract: Structural MR image (MRI) and 18F-Fluorodeoxyglucose-positron emission tomography (FDG-PET) have been widely employed in diagnosis of both Alzheimer’s disease (AD) and mild cognitive impairment (MCI) pathology, which has led to the development of methods to distinguish AD and MCI from normal controls (NC). Synaptic dysfunction leads to a reduction in the rate of metabolism of glucose in the brain and is thought to represent AD progression. FDG-PET has the unique ability to estimate glucose metabolism, providin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 97 publications
2
10
0
Order By: Relevance
“…However, accumulation of ROS begins in the neuros prior to clinical detections of signs and symptoms of NDDs particularly AD and PD [ 10 , 11 ]. When that happened, apoptotic mechanism usually switches on to eliminate neurons deemed unbearable [ 12 , 13 ], resulting to severe morphological and functional deficit, leading to progressive decline in cognitive and memory well-being [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, accumulation of ROS begins in the neuros prior to clinical detections of signs and symptoms of NDDs particularly AD and PD [ 10 , 11 ]. When that happened, apoptotic mechanism usually switches on to eliminate neurons deemed unbearable [ 12 , 13 ], resulting to severe morphological and functional deficit, leading to progressive decline in cognitive and memory well-being [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…A large number of machine learning approaches have been proposed to classify and predict AD stages (see (Falahati et al, 2014;Haller et al, 2011;Rathore et al, 2017) for reviews). Some of them make use of a single imaging modality (usually anatomical MRI) (Cuingnet et al, 2011;Fan et al, 2008;Klöppel et al, 2008;Liu et al, 2012;Tong et al, 2014) and others have proposed to combine multiple modalities (MRI and PET images, fluid biomarkers) (Gray et al, 2013;Jie et al, 2015;Teipel et al, 2015;Young et al, 2013;Yun et al, 2015;Zhang et al, 2011) . Validation and comparison of such approaches require a large number of patients followed over time.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that neuroimaging biomarkers are potential predictors of cognitive impairment (Shi et al, 2010 ; Cuingnet et al, 2011 ; Davatzikos et al, 2011 ; Falahati et al, 2014 ; Trzepacz et al, 2014 ; Bron et al, 2015 ; Jung et al, 2016 ; Lebedeva et al, 2017 ). Many researchers have developed and implemented machine learning systems which use neuroimaging biomarkers for more accurate identification of individuals with MCI or dementia (Cui et al, 2012a ; Shao et al, 2012 ; Lebedev et al, 2014 ; Min et al, 2014 ; Moradi et al, 2015 ; Yun et al, 2015 ; Cai et al, 2017 ; Guo et al, 2017 ). Early diagnosis is an essential step in the prevention and early treatment of MCI and dementia.…”
Section: Introductionmentioning
confidence: 99%